Analysis of Utilization Bandwidth and Power Transponder Extended C-Band On The Satellite Telkom 3S VSAT SCPC - Shinta Romadhona; Intan Rizqiyani Nur Faizah; Imam MP Budi (JURNAL INFOTEL, 2020)
On satellite communication systems, bandwidth and power are limited and expensive resources. Optimization of bandwidth and power utilization in Telkom 3S Satellite could be achieved if the ratio value of the percentage of bandwidth and power is 1: 1. The optimization conditions are influenced by the calculation of the link budget, the use of appropriate modulation and FEC settings. QPSK and 8-PSK modulation techniques with FEC used are ¾, 7/8, and 0.9 with a 9 m Hub antenna and VSAT SCPC with a diameter of 2.4 m and the same data rate of 1024 kbps. Based on the results of this research, the lower the modulation technique used, the lower the ratio of bandwidth and power. The most optimal FEC value to be used is 8-PSK modulation at FEC 0.93 with the resulting percentage is 97.25%, where the total carrier bandwidth generated is 93.415, and the amount of carrier power is 96.05, while the worst is modulation QPSK is at the FEC of 3/4 by producing a percentage of 35% which falls into the limited power category. Thus, the most appropriate modulation used on the Telkom 3S Satellite is the 8-PSK modulation with an FEC of 0.93.